Stability and adaptability of runner peanut genotypes based on nonlinear regression and AMMI - Santos, Roseane Cavalcanti dos; Silva, Alineaurea Florentino; Gondim, Tarcisio Marcos; Oliveira Junior, Jose Oscar Lustosa; Araujo Junior, Raimundo Bezerra de; Sagrilo, Edvaldo; Vasconcelos, Ramon Araujo de; Melo Filho, Pericles de Albuquerque; Silva Junior, Joao Luis da (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to estimate the stability and adaptability of pod and seed yield in runner peanut genotypes based on the nonlinear regression and AMMI methodologies. Yield data from 11 trials, distributed in six environments and three harvests, carried out in the Northeast region of Brazil during the rainy season were used. Significant effects of genotypes (G), environments (E), and GE interactions were detected in the analysis, indicating different behaviors among genotypes in favorable and unfavorable environmental conditions. The genotypes BRS Pérola Branca and LViPE‑06 are more stable and adapted to the semiarid environment, whereas LGoPE‑06 is a promising material for pod production, despite being highly dependent on favorable environments.